Multilevel analysis on employee wellbeing: the roles of authentic leadership, rewards, and meaningful work - Mohd Salleh, Eva Salmee; Mansor, Zuraina; Mohamed Zainal, Siti Rohaida; Md. Yasin, Ida (Asian Academy of Management & Penerbit Universiti Sains Malaysia, 2020)
Employee wellbeing (EW) is becoming a genuine concern, and it has seen a resurgence in interest with the challenges in light of industrial revolution and globalisation. There is no doubt that wellbeing of the employees is one of the secret recipes that generates high return value for all levels of chains; the individual and the organisational productivity and growth as well as nation’s prosperity. However, majority of leadership researchers have failed to capture the multi-dimensional concept of EW. Moreover, the studies of the impact of leadership styles on EW are limited and narrow-focused. Thus, this study aims to examine the role of authentic leadership (AL) style on EW. This study uses meso-mediational relationship through financial and non-financial rewards and meaningful work and how they affect EW. Data were collected from 343 employees in 30 manufacturing companies in Malaysia. The finding reveals that the positivity of authentic leaders indirectly influences EW through non-financial rewards and meaningful work. It is also suggested that financial rewards and non-financial rewards should be measured separately in consideration of current socioeconomic conditions and employees’ motivational needs.